Effect of aging on oral and written confrontation naming in Kannada and English - Thomas, Preeti T; Sam, Simmy Annie; S P, Goswami (Journal of All India Institute of Speech and Hearing, 2013)
A most common feature seen in normal individuals and disordered population’s utterance is wordfinding difficulty. The study was aimed to analyze the accuracy and type of responses and effect of aging in oral and written naming in orthographically regular language (Kannada) and irregular language (English) in bilingual individuals across age groups (25-45, 45-65, 65-85 years). Ten neuro-typical participants in each of the three age groups were studied. The stimuli included a set of twelve picture cards (nouns), which were presented individually. Two tasks were carried out in which one included the oral naming of the stimuli in one language and a simultaneous written naming in the other language. Similarly, the second task was carried out in the reverse order. The data was subjected to quantitative analysis and qualitative analysis. A significant difference (p < 0.05) was obtained within the English written naming tasks for the 65-85 years age group compared to the other age groups. With respect to the mode of response, the participants in both 65-85 years and 45-65 years age group showed a significantly better result in the English oral naming than the English written task. Qualitative analysis on the type of errors exhibited relatively higher semantic errors in the older age group. The results revealed an overall decline in the accuracy of naming responses with age. Semantic errors were more evident in the older age group for oral and written naming in both the languages. Kannada written naming was found to be better than English written naming across all the age groups, emphasizing the role of orthographic regularity in naming. This study also provides a basis that naming responses differ with the modality used for an irreregular language